Personalized auditory cues improve gait in patients with early Parkinson's disease - Li, Xinjin; Wang, Shiya; Wang, Kai; Wang, Wenjie; Tuo, Houzhen; Long, Yixin; Tan, Xiaohui; Sun, Wei (Frontiers in Neurology, 2025)
IntroductionParkinson's disease (PD) patients experience a wide variety of gait and posture problems that significantly impair their functional mobility and quality of life. Auditory cue-based training has been shown to improve gait performance in PD patients. However, most of the current methods target gains in bilateral spatiotemporal variables, whereas in the early-stages of PD, symptoms are usually unilateral.MethodsTo address the effects of unilateral onset and heterogeneity of early-stage PD on patients' gait performance, we propose a personalized training method based on auditory cues to reduce gait asymmetry between patients' right and left feet. The method targets patients' gait performance through personalized music (auditory cues) and dynamically adjusts the music based on real-time gait data to ensure synchronization with the patient's walking rhythm. Specifically, gait data are acquired in real time via Inertial Measurement Units (IMUs) attached to the ankles of the patient's right and left feet, which are used to calculate the gait cycles of the patient's right and left feet. Personalized music is then generated based on the patient's gait cycle. During the training process, the music is dynamically updated by continuously assessing the synchronization between the patient's gait cycle and the music beats.ResultsFifteen early-stage PD patients(H&Y ≤ 2.5) were initially recruited to compare and analyze the effects of training with and without auditory cues. Gait symmetry improved in all patients who received auditory cues (t = 4.9166, p = 0.0002), with a maximum improvement of 17.685%, and gait variables also showed significant enhancement. Eleven early-stage patients were then recruited for a 7-day intervention, with a mean improvement in gait symmetry of 11.803% (t = 4.391, p = 0.001). There were significant improvements in left-foot velocity (t = 4.613, p = 0.001), right-foot velocity (t = 6.250, p = 0.0001), and right-foot stride length (t = 4.004, p = 0.0025), and the average improvement rate of gait variables reached 37.947%. This indicates that the personalized training method proposed in this paper for the unilateral onset characteristics of early-stage PD is effective. It not only enhances the symmetry of walking in patients with early-stage PD, but also improves motor performance.DiscussionThe proposed method can serve as a complementary approach to pharmacological treatment in the rehabilitation of PD patients, demonstrating its effectiveness in clinical application.